Neuroscience Studies in Self Regulated Learning for Science Teacher Candidates through Optimizing the Learning Management System (LMS) with the SPADA Feature - Vica Dian Aprelia Resti; Siti Romlah Noer Hodijah; Mudmainah Vitasari (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2021)
Online learning to anticipate the Covid-19 pandemic directly or indirectly has presented a new order in the learning aspect. One of the Learning Management System (LMS) technologies used at Sultan Ageng Tirtayasa University is the Sistem Pembelajaran Daring (SPADA). Several features in SPADA have been developed to help students learn independently or guided, including summary, assignment, grade, URL and activity completion. Lecturers continue to try to anticipate problems in optimizing these features. These efforts continue to experience changes and developments because the self regulated learning that is passed by each student is not the same. This is influenced by a series of brain mechanisms in processing information or known as neuroscience. Student activities related to independent learning do not only involve cognition from a series of information processing, but a series of self-knowledge information that is included in the study of abilities and metacognitive skills. In this regard, the independence of learning in this study is explained in terms of cognitive, motivational and behavioral aspects using a questionnaire instrument and interview guidelines for 32 students in the Department of Natural Sciences Education Semester V of 2020. Based on the results and discussion, it is known that the difficulty in realizing learning independence because students do not know for sure the goals to be achieved, so it is difficult to determine various strategies for achieving them. The problem of self regulated learning encourages LMS optimization steps with SPADA features based on neuroscience studies. The first thing to do is to give students the freedom to learn according to their inclinations, so the suggestion that can be conveyed is that the lecturer should know the learning style of each student before using the LMS through the SPADA feature in developing student learning independence.